Reflections on a career in operational science: some lessons learned - Jolly, Gill (Frontiers in Earth Science, 2023)
In this short essay, I reflect on my career and some of the inspirational scientists that have influenced the way I have chosen to work. And then I highlight some of my lessons learnt as a woman scientist. Volcanology (and science more generally) as a profession has changed for the good over the last four decades, and I look forward to seeing the next generation of volcanologists drive the science forward into the future to keep communities safer from volcanic activity.